Pendidikan Kebangsaan pada Masjid Kampus Di Perguruan Tinggi Yogyakarta - Budiutomo, Triwahyu; Kaswati, Anggar; Imroatun, Imroatun; Nasruddin, Moh.; Arifin, Zainul (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
This study aims to identify the implementation of national education which is integrated in the taklim process at the campus mosque. The universities involved in this research include 4 universities in Yogyakarta. The data collection process used participatory observation, in-depth interviews and documentation of curriculum and taklim materials held at each campus mosque to be analyzed following the path of Miles and Huberman. The campus mosque taklim has not developed national education specifically but randomly with more exploration in primary literature that is directly related to the material. National insight is expanded with incidental complementary taklim such as public lectures that invite national figures as resource persons to discuss national issues. Recommendations need to equalize Islamic education with a national perspective on par with other materials that need to be complemented by the preparation of relevant materials and learning methods, not merely complementary.